Drivers of Change: Employment Responses to the Lifting of the Saudi Female Driving Ban - Abou Daher, Chaza; Field, Erica; Swanson, Kendal; Vyborny, Kate (American Economic Review, 2025)
We conduct a field experiment to quantify the impact of the lifting of the Saudi women's driving ban on women's employment by randomizing rationed spaces in driver's training. Treated women are 41 percent more likely to be employed yet are 19 percent less likely to be able to make purchases without family permission. Patterns of heterogeneous treatment effects reveal that these divergent impacts of access to driving are experienced by distinct subgroups of women. The results underscore the importance of intrahousehold responses that can counteract legal gains in women's freedoms. (JEL C93, D13, J16, J22, K38, O15, O17)